Inconsistencies and Challenges around ’Secularism’ in Nepal - Pant, Dila Datt (Journal of Tikapur Multiple Campus, 2024)
Although Nepal adopted secularism in 2015 as its official state-religion relationship, there are still several inconsistencies and challenges around it including that of freedom of religion or belief. Instead of adopting a gradual marginalization and privatization of religion as per the normative proposition of the secularism, Nepal continues to do the opposite or at times, make a fundamental departure from the notion of secular identity. The preservation and the reaffirmation of presence of religion in public sphere and preferential treatment to Hindu religion at the cost of others continues to create discrimination and pose challenges to implement secularism. These problems do not only seem to remain just non-congruent inconsistencies with the secular identity of the state at the theoretical level alone, but also seem to hinder inter-religious tolerance in practical terms such as right to freely profess, practice and preach religion, thereby impacting the lives of the religious minorities. Against this backdrop, this article examines the key legal-constitutional inconsistencies including state's practices, antagonistic socio-political narratives, and emerging challenges vis-à-vis secularism in Nepal.